Flipped Classroom in Mathematics Learning: Efforts to Improve Learning Outcomes and Self-Efficacy of MTs Students - Reza Fahrezi; Rusdi Rusdi; Tasnim Rahmat; Wikasanti Dwi Rahayu (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although low mathematics achievement and weak student self-efficacy remain persistent concerns in junior secondary education, evidence on the use of student-centered digital learning models in MTs mathematics classrooms remains limited. This study aimed to analyze the effectiveness of the Flipped Classroom learning model in improving mathematics learning outcomes and self-efficacy among eighth-grade students at MTsN 10 Agam. A quasi-experimental method with a posttest-only group design was employed. The population comprised all eighth-grade students across four classes, with class VIII.4 assigned as the experimental group and class VIII.1 as the control group through cluster random sampling. Data were collected using a mathematics achievement test and a self-efficacy questionnaire and analyzed using a t-test with SPSS. The findings showed that students in the experimental class achieved higher mathematics learning outcomes than those in the control class, with mean scores of 78.88 and 57.80, respectively, and a significant t-test result (tcount = 4.876 > ttable = 1.68). Students’ self-efficacy was also higher in the experimental class than in the control class, with mean scores of 99.04 and 92.70, respectively, supported by the hypothesis test result (tcount = 1.70 > ttable = 1.68). SPSS analysis further indicated a significance value of 0.000, confirming the effect of the Flipped Classroom model. These findings demonstrate that the Flipped Classroom learning model is effective in improving both mathematics learning outcomes and self-efficacy among MTs students. The study contributes to mathematics education by highlighting the pedagogical value of integrating technology and digital media to support independent learning, strengthen conceptual understanding, and enhance students’ confidence in their mathematical abilities.